Carcinoma Cell Hyaluronan as a ‘Portable’ Cancerized Pro-Metastatic Microenvironment - Turley, Eva A. (Cancer Res, 2016)
Hyaluronan (HA) is a structurally simple polysaccharide, but its ability to act as a template for organizing pericellular matrices and its regulated synthesis and degradation are key to initiating repair responses. Importantly, these HA functions are usurped by tumor cells to facilitate progression and metastasis. Recent advances have identified the functional complexities associated with the synthesis and degradation of HA rich matrices. Three enzymes synthesize large HA polymers while multiple hyaluronidases or tissue free radicals degrade these into smaller bioactive fragments. A family of extracellular and cell associated HA binding proteins/receptors translate the bioinformation encrypted in this complex polymer mixture to activate signaling networks required for cell survival, proliferation and migration in an actively remodeling microenvironment. Changes in HA metabolism within both the peritumor stroma and parenchyma are linked to tumor initiation, progression and poor clinical outcome. We review evidence that metastatic tumor cells must acquire the capability to autonomously synthesize, assemble and process their own ‘portable’ HA rich microenvironments in order to survive in the circulation, metastasize to ectopic sites and escape therapeutic intervention. Strategies to disrupt the HA machinery of primary tumor and circulating tumor cells may enhance the effectiveness of current conventional and targeted therapies.